ANALYSIS OF SOCIAL CHANGES IN THE REPUBLIC OF UZBEKISTAN AND ITS SPECIFIC ASPECTS - Nosirov Rashod Adilovich (American Journals Publishing, 2023)
In the article, social changes after the independence of Uzbekistan, after the independence of Uzbekistan, the history of the transition to a market economy in the society, ensuring the social protection of the population, all the reforms carried out in the country, the path of renewal and development of Uzbekistan, the history of an important part of the "Uzbek model", social protection of the population necessary measures and new Uzbekistan and the results achieved in the social sphere are analyzed.
Keywords: Reform, Uzbek model, development, strategy, development, society, state, change, history.